2007
DOI: 10.1242/dev.02781
|View full text |Cite
|
Sign up to set email alerts
|

Ptf1ais essential for the differentiation of GABAergic and glycinergic amacrine cells and horizontal cells in the mouse retina

Abstract: Basic helix-loop-helix (bHLH) transcription factors are important regulators of retinal neurogenesis. In the developing retina, proneural bHLH genes have highly defined expressions, which are influenced by pattern formation and cell-specification pathways. We report here that the tissue-specific bHLH transcription factor Ptf1a (also known as PTF1-p48) is expressed from embryonic day 12.5 of gestation (E12.5)to postnatal day 3 (P3) during retinogenesis in the mouse. Using recombination-based lineage tracing, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
183
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 29 publications
12
183
3
Order By: Relevance
“…6G-L) (Qiu et al, 2008), consistent with the abnormal differentiation of most amacrine cells in this layer of the mutant retina. It has been shown that Neurod1, Math3 and Ptf1a are required for specifying amacrine cells and Bhlhb5 and Nr4a2 for differentiation of GABAergic amacrine cells (Feng et al, 2006;Fujitani et al, 2006;Inoue et al, 2002;Jiang and Xiang, 2009;Nakhai et al, 2007). Similarly, there was a significant increase in expression of Prox1, Ptf1a, Lim1 and Ngn2, all transcription factor genes involved in horizontal cell development (Akagi et al, 2004;Dyer et al, 2003;Fujitani et al, 2006;Liu et al, 2000b;Nakhai et al, 2007;Poche et al, 2007), within the INBL of Pou4f2 null retinas (Fig.…”
Section: Safeguard Mechanism By Transcription Factors To Ensure Rgc Fmentioning
confidence: 97%
“…6G-L) (Qiu et al, 2008), consistent with the abnormal differentiation of most amacrine cells in this layer of the mutant retina. It has been shown that Neurod1, Math3 and Ptf1a are required for specifying amacrine cells and Bhlhb5 and Nr4a2 for differentiation of GABAergic amacrine cells (Feng et al, 2006;Fujitani et al, 2006;Inoue et al, 2002;Jiang and Xiang, 2009;Nakhai et al, 2007). Similarly, there was a significant increase in expression of Prox1, Ptf1a, Lim1 and Ngn2, all transcription factor genes involved in horizontal cell development (Akagi et al, 2004;Dyer et al, 2003;Fujitani et al, 2006;Liu et al, 2000b;Nakhai et al, 2007;Poche et al, 2007), within the INBL of Pou4f2 null retinas (Fig.…”
Section: Safeguard Mechanism By Transcription Factors To Ensure Rgc Fmentioning
confidence: 97%
“…In the Ptf1a-null cerebellum, Ptf1a-positive progenitors, which are normally fated to inhibitory neurons, trans-fate to excitatory granule cells (8). Cell fate changes in Ptf1a-null mice were also reported in the retina, hindbrain, and spinal cord (5)(6)(7)9). Conversely, ectopic expression of Ptf1a in neural progenitors of the dorsal telencephalon, which are normally fated to glutamatergic excitatory neurons, confers inhibitory GABA characteristics to these neurons (4).…”
Section: Ptf1amentioning
confidence: 98%
“…The fate and development of (purely) glycinergic cerebellar neurons (i.e., type 5 Golgi cells according to Simat et al (2007) has not been analyzed in Ptf1a-null mice. In the retina, Ptf1a is also critical for the development of glycinergic cells (Nakhai et al 2007). Therefore, it is tempting to speculate that Ptf1a is critical to development of all inhibitory neurons of the cerebellum.…”
Section: Development and Diverentiation Of Cerebellar (Cortical) Inhimentioning
confidence: 99%